Understanding Qualitative Research Methodology: A Systematic Review - David Seetsa Makateng; Ntsoaki Teresa Mokala (E-Journal of Humanities, Arts and Social Sciences)
As novice researchers and supervisors, the researchers of the current study have noticed that many postgraduate students encounter challenges in understanding qualitative research methodology. As such, the purpose of this work is to offer guidelines for new researchers on how to undertake and comprehend qualitative research. The main objective of this research article is to further the discussion of qualitative research principles and its essential aspects. Researchers and scholars alike make an effort to define qualitative research and the essential components of qualitative research design. This paper is a guide for inexperienced researchers because it demystifies the use of these phrases and adds to the body of knowledge by providing guidance to novice researchers as they embark on their research journey, helping them comprehend the principles and characteristics of qualitative research. The main objective of this paper is to unfold a rich understanding of qualitative research methodology, and it attempts to explore on some of key issues in regard to social explanations to novice researchers in the arena of qualitative methods, also, to practically present qualitative research method. This paper concludes by putting forward examples of when to use qualitative research methodology.